2018
DOI: 10.1111/tct.12745
|View full text |Cite
|
Sign up to set email alerts
|

Junior doctor teaching delivered by near peers

Abstract: Fifteen sessions were delivered by four tutors. All sessions received positive feedback from learners with nine sessions receiving a five out of five rating. In addition, the confidence ratings of the learners increased following each session. The tutors improved in all items of the teaching assessments and the overall rating of their teaching. Near-peer teaching could enhance the training of junior doctors DISCUSSION: The results of this pilot study suggest that the benefits described in undergraduate near-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In terms of the learner perspectives on the person delivering the teaching, it was generally felt the programme 'bene ts from teaching being delivered by senior clinicians' and there was a preference towards 'consultant lead teaching'. Sessions delivered by non-Consultants were also well received however, with a suggestion being made to 'encourage registrars to give more teaching sessions' and indeed the potential of near-peer teaching to enhance the training of junior doctors is widely described in medical education literature (7).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the learner perspectives on the person delivering the teaching, it was generally felt the programme 'bene ts from teaching being delivered by senior clinicians' and there was a preference towards 'consultant lead teaching'. Sessions delivered by non-Consultants were also well received however, with a suggestion being made to 'encourage registrars to give more teaching sessions' and indeed the potential of near-peer teaching to enhance the training of junior doctors is widely described in medical education literature (7).…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that teaching skills in various domains and the confidence of learners were measurably improved through the programme. The authors suggested that positive effects of near‐peer programmes on teaching skills could enhance professional training . Systematic review evidence reports benefits for students in professionalism, academia and affect, and benefits for near‐peer teachers in affect, communication and social skills .…”
Section: The Evidence Behind Near‐peer Teachingmentioning
confidence: 99%
“…There is no universally accepted definition of what near-peer teaching is: the concept has been variously described as 'an approach where the teacher is at least one year senior to the learner', 1 'trainees teaching more junior trainee colleagues', 2 and 'a form of teaching where students are instructed by other students' . 3 A comprehensive definition, however, is as follows: 'people from similar social groupings who are not professional teachers helping Editor's note: Near-peer teaching (NPT) and peer-assisted learning (PAL) are topics that have frequently featured in The Clinical Teacher and other education journals in the last few years.…”
Section: What Is Near-peer Teaching?mentioning
confidence: 99%
See 1 more Smart Citation
“…without faculty input) (Bowyer & Shaw 2021), and few programmes offer formal opportunities to prepare students for their roles as teachers after graduation (McKenna & French 2011;Spies et al 2021). Furthermore, NPT is often initiated as a costeffective measure to address increasing student numbers, rather than by the educational promise behind this approach (Anyiam et al 2018;Burgess et al 2014;De Menezes & Premnath 2016;Mutwali & Hassan 2013;Taylor et al 2013;. Similarly, the NPT programme reported in this study was developed because of financial constraints resulting from increasing class sizes requiring additional clinical educators.…”
Section: Theme 1 Near-peer Teaching Introductionmentioning
confidence: 99%